La Belgique sous les nazis : 1. 1940-1941 - Delandsheere, Paul; Ooms, Alphonse (Bruxelles : L'Edition Universelle, 1946)
Bibliotheek Camille Huysmans
Frans
Meerdelige publicatie
Keywords: Wereldoorlog 2; België